Geopolitics of the Prespa Agreement: Background and After-Effects. Issue 3 (3rd May 2020) - Vankovska, Biljana
ABSTRACT: The Prespa Agreement (PA), which allegedly resolved the name dispute between Athens and Skopje, has been commended as an unparalleled triumph of Western diplomacy and a proof of maturity on the part of the two states involved. This article sheds light on one of the deal's least explored aspects—its geopolitical motives. The starting premise is that the agreement is a product of arm-twisting for the sake of advancing NATO, i.e., predominantly USA interests in the region. This article argues that instead of resolving a dispute, the PA is likely to grow into an additional source of regional destabilization. This article handles the PA, the conditions under which it was made possible and its aftermath, as an empirical case that may expose some important points about how neo-imperialism organizes matters in the region and beyond.